Justice climatique et démocratie environnementale - Les inégalités d’accès au droit des populations vulnérables aux risques littoraux – quelques éléments de comparaison - Marie-Laure Lambert; Aurélie Arnaud; Cécilia Claeys (VertigO)
The environmental democracy, as promoted by the Aarhus convention (access to environmental information, participation in the public decisions and access to the judge), encounters, in reality, economic and social inequalities. In particular, as regards littoral risks in a context of climate change, the exposed populations are not equal, including on the French territory. Examples studied on the Basque and Guadeloupean coasts, help to compare the cases of populations who appear to be very different in terms of environmental, social, economic and legal vulnerability. Once analyzed these elements, it is useful to think of the definition of the general interest which should condition the public operations of coastal protection or relocalization of the exposed housings. However, this general interest is never defined, and rather appears, in many cases, as a plurality of private interests of owners having robust « capabilities », reinforced by the high value of their goods. A more thorough reflection will have to be carried out, in order to found climate change adaptation of the territories, on criteria of equity which make it possible to put firstly in security the most vulnerable people.